Duration Of Treatment Hours And Level Of Dependence Of Cancer Patients Affect Caregiver’s Stress Level - Yesiana Dwi Wahyu Werdani (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2020)
Cancer is a disease with complex side effects that can interfere with the body functions, impacting on increasing patient dependence on caregivers. This study objectives was to prove the duration of treatment hours and the level of dependence of cancer patients affect caregiver’s stress level. This was a cross-sectional study. Population 50 caregivers who live at the Indonesian Cancer Foundation East Java Branch Surabaya Indonesia and only 30 samples were chosen based on inclusion criteria. Instruments used duration of treatment hours questionnaire, KATZ index and caregiver stress self-assessment. All instruments had been tested validity and reliability. Ethical procedures were done before the research starts. After the data collected it was analyzed used a multinomial logistic regression test with p < 0.05. The majority of participants taking care of cancer patients for 4 – 6 hours/day (56.7%), most of the cancer patients who treated by caregivers, experienced moderate levels of dependence (50%) and the majority of caregivers experienced stress at moderate levels (56.7%). There was a significant effect between the duration of treatment hours and the level of dependence of cancer patients on the caregiver’s stress level. The duration of treatment hours affect 34.3% on caregiver’s stress level (p = 0.03) and level of patient’s dependence affect 41.9% (p = 0.01). The longer hours of care lead to less caregiver’s free time for their personal needs, so that most of the time is used for patient care. Likewise, the higher the level of patient dependence on caregivers, the more time is given for care and can further trigger stress on caregivers.